DeLIVERing an introduction to psycho-collocations with SIAB in White Hmong - Jaisser, Annie (2024)
In Western cultures the heart is typically considered to be the primary seat of the emotions: In contrast, in Hmong culture, LUB SIAB 'the liver' is viewed as the locus of choice (LUB being the classifier associated with SLAB in this case).